An Evaluation Study of Backward Regions Grant Fund (BRGF) - Planning Commission (Planning Commission, 2018)
Bridging regional development disparities is one of the important objectives of planning in India. There are about 200-250 districts, which are backward on various indicators of socio-economic development and the level of infrastructure. These districts invariably fall in the backward states, and are heavily populated by the Scheduled Castes, Scheduled Tribes and Muslim minorities (in Eastern India). There is a heavy concentration of the poor people among the above communities particularly among those living in the backward regions. While there has been an increase in personal, sectoral and regional inequalities in recent years, the Government of India has increased programme based interventions to mitigate the consequences of increasing inequalities.
Planning Commission Government of India Institute for Human Development
Planning Commission Government of India Institute For Human Development